Diagnosis and management of congenital floor of mouth masses: A systematic review. (January 2021) - Lucas, Jordyn P.; Allen, Meredith; Siegel, Bianca; Gonik, Nathan
Abstract: Objectives: Determine the utility of preoperative imaging and the optimal course of management for congenital floor of mouth (FOM) cysts in infants. Methods: A systematic review of the literature was performed conforming to PRISMA guidelines. Pubmed, Embase and Cochrane Library databases were queried to identify cases of infants with congenital floor of mouth masses. Patient demographics, presenting findings, imaging, management, complications, and outcomes were determined. Results: 85 patients were evaluated. 98% of patients presented at 16 months of age or younger. The most common presenting symptom was submental mass or swelling, 31.3%. Among the patients that underwent imaging, the suspected diagnosis obtained from imaging findings was consistent with the final pathologic diagnosis 59% of the time reported and inaccurate 34% of the time. There were multiple definitive treatment modalities described in the literature review including surgical excision, 82.3%, marsupialization, 12.9%, chemical injection 2.3%, sclerotherapy 1.2%, % and radiation, 1.2%. Recurrence rate after initial definitive treatment was as follows, surgical excision, 8.8%, marsupialization, 80%, sclerotherapy, 100%, chemical injection, 50%, and radiation, 100%. Conclusion: Preoperative imaging studies should not be relied upon alone to determine suspected pathology and subsequent management in pediatric patients with FOM masses. It may be beneficial for these patients to undergo primary surgical excision regardless of imaging studies or suspected pathology. Needle aspiration offers limited addition to pathologic diagnosis and should only be performed in the setting of acute symptomatic management. Surgical excision should be considered as definitive treatment modality in all patients with FOM masses, regardless of the suspected diagnosis of ranula. Further multi-institutional cohort studies could be invaluable to elucidate definitive treatment guidelines in this patient population.